Distribusi Foraminifera Bentik Resen di Perairan Lombok (Suatu Tinjauan di Daerah Gili Air, Gili Meno dan Gili Trawangan) - Suhartati M Natsir (Fakultas Biologi | Universitas Jenderal Soedirman, 2010)
Study on distribution of benthic foraminifera in Gili Air, Gili Meno and Gili Trawangan,Lombokwas held on February 12 – 15, 2008. Samples were collected respectively in the each side, including Northern, Eastern, Southern and Western part of Gili by using Van Veen Grab. Every side of the islands was collected three samples within 10 meters of clearance of each location. Thus, the collected samples of the three Gili were totally on 36 samples. The ecological parameters were also being measured, i.e. depth, temperature, salinity, pH and turbidity. The number of collected specimens of foraminifera was totally 46197 and the most specimen belongs to Suborder Rotaliina (423026 specimens). Then, 2137 specimens were recognized under Suborder Milioliina and the others 1036 specimens belong to Suborder Textulariina. The collected specimens consist of 49 species of 29 genera, which composed from Suborder Rotaliina (25 species in 20 genera), Suborder Milioliina (20 species, 7 genera) and Suborder Textulariina (4 species 2 genera).